Cash Disbursement Accounting Systems and Procedures from a Sharia Accounting Perspective - Hanin, Haya Fadiyah; Kamilah, K (Institut Bisnis dan Informatika Kesatuan, 2024)
Association financial systems require bookkeeping data to handle administrative and financial issues. This system is a collection of elements that are interrelated, have the same function and purpose, and were created to handle something that happens regularly. This system processes data (input) into data (output) in the form of financial reports. This research aims to analyze the implementation of the cash disbursement system and procedures at the Health Office of Medan City. The study focuses on the challenges of implementing the financial system, dynamic regulatory changes, and technological aspects that may affect financial management efficiency. Using a qualitative descriptive and quantitative survey method, observations, interviews, and document analysis were conducted to gain an in-depth understanding of the financial system's implementation in the Health Office. The research results classify several stages in cash disbursement and identify obstacles and potential improvements in the process and must comply with sharia accounting principles in the form of fairness, transparency and accountability. This study is expected to make a positive contribution to enhancing financial management efficiency and transparency in the healthcare sector.